(untitled) (Modern education and development, 2025)
This article sheds light on the effective strategies for teaching writing in educational settings, highlighting the significance of a process-oriented approach that consists of prewriting, drafting, revising, editing, and publishing. It emphasizes the integration of technology to foster student engagement and facilitate real-time feedback through tools like word processors and online collaboration platforms. The article also underscores the importance of formative assessment techniques, such as writing conferences and peer reviews, to support personalized feedback and track student progress.